Partner Selection in the Open Innovation Process - Sopińska, Agnieszka; Mierzejewska, Wioletta (Studia Oeconomica Posnaniensia, 2017)
The article discusses the issue of selecting partners in an open innovations process on theoretical and empirical grounds. Presents the phenomenon of innovation in the context of the strategic choice of modern companies, reveals the essence of open innovation versus the closed model, and outlines the ways and criteria for selecting partners in open innovation process described in the literature. The results of the quantitative research carried out in the years 2015-2016 in innovative companies operating in Poland are presented in the empirical part of the article. The analysis revealed the categories of players involved in creating open product and process in-novations, their role in initiating innovation processes, and the level of engagement of each external partner. It was found that the initiative of creating open innovations on the Polish market belongs to the companies themselves and not to external partners. External partners are selected primarily from neighbouring economic pathways (suppliers and customers), and their choice is determined by previous collaborative experiences. Innovative companies operating on the Polish market are very reluctant to cooperate with other categories of potential partners: competitors, self-government units, online communities or scientific research institutions.